The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/joor.12499
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture on pain comorbidity in women with and without temporomandibular disorder‐pain

Abstract: Evidence on cultural differences in prevalence and impact of common chronic pain conditions, comparing individuals with temporomandibular disorders (TMD) versus individuals without TMD, is limited. The aim was to assess cross-cultural comorbid pain conditions in women with chronic TMD pain. Consecutive women patients (n = 122) with the index condition of chronic TMD pain diagnosed per the research diagnostic criteria for TMD and TMD-free controls (n = 121) matched for age were recruited in Saudi Arabia, Italy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Interestingly, Italians take antidepressants significantly more than the two other sites. A possible explanation could be that in the current study, Italians experienced greater interference of pain in their daily living according to the GCPS score (III‐IV) compared to Saudis and Swedes . However, it must be stressed that in the questionnaire, the patients were asked about treatment modalities for TMD, and while antidepressant use could have been for depression rather than TMD, it is also likely that the antidepressant use was for pain or for pain‐related mood changes, consistent with the self‐report by the participants.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Interestingly, Italians take antidepressants significantly more than the two other sites. A possible explanation could be that in the current study, Italians experienced greater interference of pain in their daily living according to the GCPS score (III‐IV) compared to Saudis and Swedes . However, it must be stressed that in the questionnaire, the patients were asked about treatment modalities for TMD, and while antidepressant use could have been for depression rather than TMD, it is also likely that the antidepressant use was for pain or for pain‐related mood changes, consistent with the self‐report by the participants.…”
Section: Discussionsupporting
confidence: 60%
“…Table lists demographic and pain characteristics for the patients from the three cultures and was presented in a previous study by the same authors . Italian patients were significantly older than Saudi ( P < 0.01) or Swedish patients ( P = 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies consistently report that TMD symptoms exhibit significant statistical overlap with other chronic pain conditions, 25 suggesting the existence of common etiologic pathways. 1 Most studies of overlap with orofacial pain have focused on selected pain conditions, classified according to clinical criteria (eg, headaches, cervical spine dysfunction, and fibromyalgia 5 ), location of self-reported pain (eg, back, chest, stomach, and head 2 ), or the number of comorbid pain conditions. 11 Although there is a long tradition of depicting overlap between pain conditions qualitatively using Venn diagrams, 28 we know of few studies that have quantified the degree of overlap between TMD and pain at multiple locations throughout the body.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, 7,8 however, have shown that socioeconomic level could affect TMD. The emotional characteristic of pain, which is strongly influenced by culture, may lead to behavioral modification or heightened awareness, which may increase the prevalence of comorbidities, as a consequence of exposure to the environment; pain processing (which differs among cultural groups), the manner in which pain is interpreted; 16 and adaptive capacity. 15 Sociodemographic factors are potential mitigators or exacerbators of menopausal symptoms 10 because they influence not only women's lifestyle but also their quality of life, and the same can be said about TMD-induced complaints.…”
Section: Temporomandibular Disorder and Menopausementioning
confidence: 99%